Culture, Technology and the New Death: Deadly Disputes in Japan and North America - Lock, Margaret (Culture, 1997)
"Brain death" was institutionalized 25 years ago primarily to make organs "harvested" from brain dead bodies on an artificial ventilator available for transplant. Doubts exist as to whether the donors used in the first heart transplants conducted in South Africa in 1967, and in Japan in 1968, were dead. Reaction to these two experiments was remarkably different. In Japan the surgeon was arrested for murder, a national debate about brain death continues today, and transplants from brain dead bodies have only been made permissible since June 1997. This debate contrasts with that in North America, where transplant technology is routinized and an organ "shortage" is recognized. In Japan the argument is politicized, focuses on death, and draws on cultural knowledge about Self and Other; Japan and the West; harmony and individualism; tradition and modernity / postmodernity. North American discussion focuses on saving lives; making death meaningful; remaking death yet again; and assumes technology to be culturally and politically autonomous. These respective debates are discussed using textual analysis and the results of interviews with philosophers, physicians, and nurses in both cultural settings. An effort is made to suggest why the Japanese debate is central in constituting contemporary cultural identity, whereas the North American debate is of little public interest. The significance for anthropology of the hybrid status of brain dead bodies and organ recipients together with the national and global circulation and commodification of bodies and body parts associated with this technology is considered.